Stimulation in Supplementary Motor Area Versus Motor Cortex for Freezing of Gait in Parkinson's Disease - Kim, Sang Jin (J Clin Neurol, 2018)
BACKGROUND AND PURPOSE: Freezing of gait (FOG) is a frustrating problem in Parkinson's disease (PD) for which there is no effective treatment. Our aim was to find brain stimulation areas showing greater responses for reducing FOG. METHODS: Twelve PD patients with FOG were selected for inclusion. We explored the therapeutic effect of repetitive transcranial magnetic stimulation (rTMS) in the supplementary motor area (SMA) and the motor cortex (MC). We measured the number of steps, completion time, and freezing episodes during the stand-walk-sit test before and after rTMS treatment. We also tested freezing episodes in two FOG-provoking tasks. RESULTS: There was a trend for a greater reduction in freezing episodes with SMA stimulation than MC stimulation (p=0.071). FOG was significantly improved after SMA stimulation (p<0.05) but not after MC stimulation. CONCLUSIONS: Our study suggests that the SMA is a more-appropriate target for brain stimulation when treating PD patients with FOG. This study provides evidence that stimulating the SMA using rTMS is beneficial to FOG, which might be useful for future developments of therapeutic strategies.